Experimental determination of the relationship between the elements of a back-to-back diode model for organic photovoltaic cells’ S-shaped I-V characteristics and cell structure - Elisa Sesa; Darmawati Darwis; Xiaojing Zhou; Warwick J. Belcher; Paul C. Dastoor (AIP Advances, 2019)
Equivalent circuit models are becoming increasingly important for the development of large scale demonstrations of organic photovoltaics. The ‘S’ shaped profile is a common feature of OPV current-voltage (I-V) curves and consequently equivalent circuit models that replicate these features are urgently required. In this paper we prepare a case study based on ITO/PEDOT-PSS/P3HT:PCBM/Al devices whose I-V profiles transition from ‘S’ shape to ‘J’ shape with increasing aluminium thickness prepared using low evaporation rates. We show that the new back-to-back diode model (B2BDM) not only faithfully models these I-V profiles but, more importantly, that the specific circuit elements in the model directly correlate with the physical structures in OPV devices that determine the ‘S’ shaped character. On the basis of these observations, the physical interpretation of the B2BDM is discussed.